Nominal wage rigidity in the EU countries before and after the Great Recession: Evidence from the WDN surveys - Eva Branten; Ana Lamo; Tairi R\~o\~om (European Central Bank (ECB), 2018)
This paper studies the recent trends in nominal wage rigidity in a large group of EU countries, using survey data. We analyse two forms of nominal wage rigidity: downward nominal wage rigidity (DNWR) and the lagged response of wages to shocks. The frequency of wage changes, which is an indicator of lagged wage setting, slowed down in the aftermath of the Great Recession. We assess the possible reasons for this and show that it was at least partially caused by a combination of a decline in average wage growth and persistent DNWR. In countries where wage growth slowed down more after the Great Recession, the frequency of wage changes declined more steeply as well. Our data allows evaluating the prevalence of DNWR in diverse economic circumstances. Like earlier research on this topic, we find that DNWR tends to be strongly prevalent, even in periods of slow economic growth and low wage inflation. DNWR declines during severe recessions but even then wage setting does not become completely flexible as the proportion of observed wage cuts is still below the level that would correspond to a flexible regime.
Keywords: B41; D22; 330; downward nominal wage rigidity; wage change frequency; survey